Potential Mapping And Development Strategy Of Karang Joang Village As A Tourism Village Claster Of Sustainable Tourism Support Towards Sungai Wain (Hlsw) Protected Forest In Balikpapan - Zulfaidah Penata Gama (Journal of Innovation and Applied Technology, 2018)
Wain River Protected Forest (HLSW) has a very high biodiversity of flora and fauna, but the potential for natural tourism has not received maximum attention in the District of North Balikpapan, as evidenced by the relatively small number of domestic and foreign tourist visits. Therefore the purpose of this activity is to find out the potential and strategies of community development at HLSW locations. Stakeholder analysis is carried out to manage potential conflicts that are expected to hinder the resolution of social and environmental problems that occur in the community. The analysis includes three stages, namely stakeholder inventory, analysis of influences and interests, and identification of participation. Strategic and concrete steps can be taken by providing revolving grants to the community, priority in handling environmental problems, negotiating with relevant parties who care about environmental and social issues, community assistance models to create a clean and healthy environment. The community empowerment model is economically independent, Community-based ecotourism model for improving the welfare of the people of Karang Joang Village Environmental awareness model for elementary school children as environmental ambassadors in Karang Joang Village, North Balikpapan Sub-District, Balikpapan City.